The Dethronement of the Lion - a Commentary - Thorsen, Liv Emma (Tidsskrift for kulturforskning, 2008)
The Dano- African lions that were imported to Kristiansand Zoo and Amusement Park a year ago are thriving. Four cubs were born on the first day of June and the happy news received a lot of media attention: For the first time in history, presumably, a lioness has given birth to offspring in Norway, and we are all welcomed to propose names for the newborn cubs (VGNett 2008). Quite a peculiar episode seen from a faunal point of view, since the most polarized question in the domestic debate on indigenous predators is whether the wolf should be allowed to propagate within Norway’s borders. The trouble is that wolves are not yet kept in cages, and when a she-wolf has a litter, her cubs are not the object of naming competitions.